Determination of Secondary School 4th Grade Students’ Mental Models of the Astronomer - Meryem Görecek Baybars; Büşra Tuğçe Kayabas (Institute of Advanced Engineering and Science, 2018)
Teaching astronomy to young generations is of great importance because astronomy education helps us to better understand the world we are living in and to find answers to our questions. In this regard, the current study aimed to determine the secondary school 4th grade students’ mental models of the astronomer. The current research is designed as a descriptive study employing the special case study method. The study was conducted in a city located in the western part of Turkey. The study group is comprised of a total of 77 secondary school 4th grade students attending a state school. In line with the purpose of the study, a data collection tool consisted of 2 open-ended questions was developed. In light of the findings of the study, it can be argued that the mental models possessed by the students about the astronomer are the scientific model, the astronaut model and the celestial bodies model